Genetic diversity of upland rice germplasm distributed in Latin America - Guimarães, Elcio Perpétuo; Borrero, Jaime; Ospina-Rey, Yolima (Pesquisa Agropecuaria Brasileira, 1996)
Narrow genetic base has been a concern in irrigated rice. Upland rice varieties in Latin America show a similar trend. The parentage of 2,061 upland crosses and 271 advanced lines that CIAT (Centro Internacional de Agricultura Tropical) distributed to partners was traced back to the immediate parents; the yearly percentage participation was estimated. The main objectives were to assess the genetic variability used and distributed by CIAT, to identify reasons why genetic diversity is eliminated, and to propose alternatives for broadening the genetic base. African germplasm contributed to 46.0% of the parents used in crosses and 34.6% in the advanced lines. A maximum of 12 and a minimum of 4 lines were necessary to make up 50% of the participation frequency in crosses every year; globally it required 16 lines. Intense selection pressure for agronomically important traits, such as plant type and blast resistance, eliminated between 17.6 and 69.0% of the early segregating lines every year. Sharing germplasm at early stages of development and population improvement through recurrent selection are alternatives that offer broad-base germplasm to Programs in Latin America.